Implementation of treatment escalation plans in an old age psychiatry inpatient hospital - Jay Amin; Victoria Osman-Hicks; Harnish P Patel; Anne Y T Chua; Adnaan Ghanchi; Sangeeta K Makh; Jessica Grayston; Stephen J Woolford; Sahan Wijayaweera (BMJ Open Quality)
A treatment escalation plan (TEP) enables timely and appropriate decision making in the management of deteriorating patients. The COVID-19 pandemic precipitated the widespread use of TEPs in acute care settings throughout the National Health Service (NHS) to facilitate safe and effective decision making. TEP proformas have not been developed for the inpatient psychiatric setting. This is particularly concerning in old age psychiatry inpatient wards where patients often have multiple compounding comorbidities and complex decisions regarding capacity are often made. Our aim for this quality improvement project was to pilot a novel TEP proforma within a UK old age psychiatry inpatient hospital. We first adapted a TEP proforma used in our partner acute tertiary hospital and implemented it on our old age psychiatry wards. We then further refined the form and gathered data about uptake, length of time to complete a TEP and the ceiling of care documented in the TEP. We also explored staff, patient and family views on the usefulness of TEP proformas using questionaries. TEP decisions were documented in 54% of patient records at baseline. Following revision and implementation of a TEP proforma this increased to 100% on our two wards. The mean time taken to complete a TEP was reduced from 7.1 days to 3.2 days following inclusion of the TEP proforma in admission packs. Feedback from staff showed improvements in understanding about TEP and improved knowledge of where these decisions were documented. We advocate the use of TEP proformas on all old age psychiatry inpatient wards to offer clear guidance to relatives and treating clinicians about the ceilings of care for patients. There are potentially wider benefits to healthcare systems by reducing inappropriate transfers between psychiatry and acute NHS hospitals.